Analisis Tema Dalam Artikel Majalah Pariwisata: Garuda “Masks, Malang’s Traditional Icon” dan Terjemahannya - Titik Akriningsih (Jurnal Pariwisata Indonesia, 2013)
Systemic Functional Linguistics (SFL), as pioneered by Halliday, has gained a significant position among other theories in linguistics. This theory views language as a social semiotic resource utilized to accomplish people’s purposes by expressing meanings in context. This paper attempts to discuss theme in an English text translated into Indonesian and the shift of it. The source text in this study is an article entitled Masks, Malang New Icon which appears on a tourism magazine, and the target text is the Indonesian version of the article which appears on the same magazine. All languages the clausa has the character of a message. That’s why the clausa is organized as a message by having a special status assigned to one part of it. The special status is called theme. Every text has its own characteristic of theme to organize message. There are many themes appears on both the article being analyzed. The use of certain theme becomes the writer’s reason and strategy to express social process.